Implementation of Creative Economy in Improving Economic Welfare Maqāṣid Al-Sharīʿah Perspective (Case Study: Rattan Craftsmen of Jentera Stabat Village) - Nurhalita, Siti; Marliyah, Marliyah (Universitas Alma Ata, 2023)
Creative economy development can increase people's income in Jentera Stabat Village, which is one of the Creative Economy Areas, where almost every family becomes a rattan woven craftsman. UD. The Ambane area is one of the places where creative economic industry activities develop, especially rattan woven craftsmen. UD. Medan Ambane seeks to provide proper wages to rattan-woven craftsmen so that their lives can be more prosperous. The wages of the rattan woven craftsmen are 250,000 - 400,000 set with a processing time of around 5 - 7 days depending on the complexity of the pattern and the shape of the woven. This study aims to determine the increase in the economic welfare of rattan craftsmen from the perspective of machair sharia and the creative economy. This research is qualitative research using a descriptive approach, resulting in an in-depth description of the welfare of the rattan craftsmen in Jentera Stabat Village. To obtain data, researchers used an instrument in the form of in-depth interviews. So the results of the study indicate that the wicker rattan chair business is carried out by UD. Ambane event from the perspective of sharia maqhasid has brought positive changes because the existence of a wicker chair business plays a role in increasing people's income and can create jobs for the surrounding community. Based on maqhasid sharia according to Ibnu Asyur who applies 8 elements related to employment, it is concluded that UD. The Ambane event in Muamalah Intensification provides direct training to craftsmen, and for Gharar which is difficult to avoid by UD's business. The Ambane event does not burden every small mistake made by the craftsmen because the business owner will provide the right solution. Owner of UD. The Ambane event also provides working hours from morning to night according to the needs of the craftsmen provides decent wages, and avoids elements of slavery.